On logical and empirical slippery slopes - Wieczorek, Krzysztof A. (Folia Philosophica, 2012)
The paper addresses so-called slippery slope arguments, which are usually used as warnings against accepting a certain view or undertaking some action for the reason of their negative consequences. Two types of this kind of arguments might be recognised, which differ significantly: logical and empirical one. Logical slippery slopes are rarely well supported. Most common flaw they contain is so-called fallacy of assimilation. Empirical slippery slopes, on the other hand, are definitely much more powerful kind of argument. Their soundness depends on the truth of premise according to which decision A1 will finally lead to unwanted outcome An. Yet, the assessment of this premise, and in consequence of the entire argument, often demands specialist knowledge in the field.